Advancement of thyroid surgery video recording: A comparison between two full HD head mounted video cameras. (May 2017) - Ortensi, Andrea; Panunzi, Andrea; Trombetta, Silvia; Cattaneo, Alberto; Sorrenti, Salvatore; D'Orazi, Valerio
Abstract: Background: The aim of this study was to test two different video cameras and recording systems used in thyroid surgery in our Department. This is meant to be an attempt to record the real point of view of the magnified vision of surgeon, so as to make the viewer aware of the difference with the naked eye vision. Materials and methods: In this retrospective study, we recorded and compared twenty thyroidectomies performed using loupes magnification and microsurgical technique: ten were recorded with GoPro ® 4 Session action cam (commercially available) and ten with our new prototype of head mounted video camera. Results: Settings were selected before surgery for both cameras. The recording time is about from 1 to 2 h for GoPro ® and from 3 to 5 h for our prototype. The average time of preparation to fit the camera on the surgeon's head and set the functionality is about 5 min for GoPro ® and 7–8 min for the prototype, mostly due to HDMI wiring cable. Videos recorded with the prototype require no further editing, which is mandatory for videos recorded with GoPro ® to highlight the surgical details. Conclusion: the present study showed that our prototype of video camera, compared with GoPro ® 4 Session, guarantees best results in terms of surgical video recording quality, provides to the viewer the exact perspective of the microsurgeon and shows accurately his magnified view through the loupes in thyroid surgery. These recordings are surgical aids for teaching and education and might be a method of self-analysis of surgical technique. Highlights: Head mounted video recording have been used in the most varied fields of surgery. Head mounted video camera - new prototype - attempts to record the real point of view of the magnified vision of surgeon. Head mounted video camera - new prototype - shows the difference between magnified vision and the naked-eye vision. Head mounted video camera - new prototype - is better than conventional video cameras in surgical education and training.